Rapport sur le Forum sur l'éducation et la vitalité - Macris, Antonia; O'Donnell, Lorraine; Shoumarova, Lina; Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Du 3 au 5 novembre 2021, des chercheurs, des praticiens, des intervenants communautaires et des décideurs des quatre coins du Québec se sont réunis virtuellement à l’occasion d’un évènement de trois jours intitulé Forum sur l’éducation et la vitalité : Soutenir l’éducation des minorités de langue anglaise au Québec. Il s’agissait du deuxième forum organisé par la Table d’éducation interordres (ILET), un comité du Réseau de recherche sur les communautés québécoises d’expression anglaise (QUESCREN) de l’Université Concordia, et il avait pour objectif d’encourager la mobilisation en vue d’élaborer au Québec une offre d’enseignement en langue anglaise qui soit saine et viable et favorise la persévérance scolaire, l’accès à de bons emplois dans la province et un fort sentiment d’identité et d’appartenance. Le présent rapport donne une vue d’ensemble du Forum et des principaux messages à retenir.
Keywords: Official Language Minority Community (OLMC)

Report on the Education and Vitality Forum - Macris, Antonia; O'Donnell, Lorraine; Shoumarova, Lina; Donovan, Patrick (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
From November 3 to 5, 2021, researchers, practitioners, community stakeholders, and policy makers from across Quebec gathered virtually for a three-day event entitled Education and Vitality Forum: Supporting English-Language Minority Education in Quebec. This was the second forum convened by the Inter-Level Educational Table (ILET), a committee of the Quebec English-Speaking Communities Research Network (QUESCREN) at Concordia University. Its objective was to encourage mobilization around the development of a healthy and sustainable English-language educational offer in Quebec that supports student retention, access to good jobs in the province, and a strong sense of identity and belonging. This report provides an overview of the Forum and key takeaway messages from it
Keywords: Official Language Minority Community (OLMC)

Quebec Online Alliance (QOA) - the Online Campus for Students with Medical Exemptions from the English School Boards Across Quebec Officially Opened this Week - Leading English Education and Resource Network (LEARN) (2021)

Brief Presented to The House of Common Standing Senate Committee on Official Languages Submitted by the Quebec English School Boards Association - Quebec English School Boards Association (2021)
The Quebec English School Boards Association was founded in 1929. The role of the association is to represent the nine English school boards of Québec as well as the Littoral School Board, a special status school board. Our member boards cover the full geographic territory of Québec with some board territories covering more than 400,000 square kilometres, equal to the land area of Spain. Our board student enrolments range from 1,300 (Eastern Shores in the Gaspé region) to more than 25,000 for each of the 2 boards serving the Island of Montr al. Our network is comprised of about 340 schools and adult centres, some with enrolment well below 100 to as many as 2,000. Our boards serve the youth sector from Kindergarten to Secondary V (grade 11). They also deliver Adult Education and Vocational Training. Some of our boards offer pre-kindergarten programs to 4-year-old children and the Adult and Vocational sectors cater to students 16 years of age and older. All told there are approximately 100,000 students in the minority-language English public school system.
Parallel title: English and French : Towards Real Equality of Official Languages in Canada

QCGN Statement on Superior Court Ruling on Quebec’s Secularism Law : A Good Day for Minority Education Right - Quebec Community Groups Network (QCGN) (2021)

Baisse des effectifs dans le secteur scolaire anglophone du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
La Charte de la langue française (1977)1, également connue sous le nom de Loi 101, a eu un impact fort et durable sur les écoles publiques de langue anglaise2. En vertu de cette loi, les élèves de la maternelle au secondaire dont les parents ou les frères et sœurs canadiens ont été instruits au Canada en anglais ont droit à une éducation publique en anglais. À quelques exceptions près, tous les autres élèves doivent fréquenter des écoles de langue française. Ces clauses éducatives limitent l’accès aux écoles de langue anglaise3 en orientant les enfants d’immigrants nouvellement arrivés vers les écoles publiques de langue française4, ainsi que l’accès des Québécois francophones qui n’ont pas des membres de leurs familles qui ont fréquenté des écoles de langue anglaise.
Parallel title: Résumé de recherche en éducation no 1
Keywords: Official Language Minority Community (OLMC)

Challenges Around Resources and Services in Quebec's English-language Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
English-language schools in Quebec struggle with diverse challenges, from urban and rural poverty to being located in isolated and remote areas. These issues impact the services and resources available to students and schools already constrained by a declining student population (Advisory Board on English Education [ABEE], 2018).
Parallel title: Education Research Brief no. 3
Keywords: Official Language Minority Community (OLMC)

Decline of Enrolment in Quebec's English-language School Sector - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The Charter of the French language (1977),1 also known as Bill 101, has had a strong and lasting impact on the English-language public school sector.2 Under this law, kindergarten to secondary school students whose Canadian parents or siblings were educated in Canada in English are entitled to English-language public education. Aside from a few exceptions, all other students must attend French-language schools. These educational clauses limit access to English-language schools3 by routing the children of newly arrived immigrants to French-language public schools,4 as well as restricting the access of Francophone Quebecers with no family history of attending English-language schools.
Parallel title: Education Research Brief no. 1
Keywords: Official Language Minority Community (OLMC)

Les enjeux en matière de ressources et de services dans les écoles de langue anglaise du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Ces enjeux ont un impact sur les services et les ressources disponibles pour les élèves et les écoles, déjà fragilisés par un effectif scolaire en constante diminution (Commission de l’éducation en langue anglaise [CELA], 2018).
Parallel title: Résumé de recherche en éducation no 3
Keywords: Official Language Minority Community (OLMC)

Prestation de services aux élèves ayant des besoins particuliers dans les écoles publiques anglophones du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Au Québec, un nombre croissant d’élèves sont identifiés comme ayant des besoins particuliers et on estime actuellement que cette population représente un élève sur cinq (20,4 %) dans le système scolaire public (Commission des droits de la personne et des droits de la jeunesse [CDPDJ], 2018).
Parallel title: Résumé de recherche en éducation no 4
Keywords: Official Language Minority Community (OLMC)

Provision of Services to Special Needs Students in Quebec's English-language Public Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
In Quebec, a growing number of students are identified as having special needs, and it is currently estimated that this population represents one in five students (20.4%) in the public school system (Commission des droits de la personne et des droits de la jeunesse [CDPDJ], 2018).
Parallel title: Education Research Brief no. 4
Keywords: Official Language Minority Community (OLMC)

Postsecondary Education in the Minority Language : An Overview and Analysis of the Issues - Mariève, Forest; Deschênes-Thériault, Guillaume (Sociopol, 2021)
The advocacy efforts of Francophone minority communities (FMCs) that followed the adoption of the Official Languages Act (1969) and the Canadian Charter of Rights and Freedoms (1982) led to the development and implementation of the provincial and territorial minority-language elementary and secondary school systems. In Quebec, the implementation of the Englishlanguage elementary and secondary school system did not meet with the same level of resistance as that faced by the French-language school systems in FMCs.
Parallel title : Report Prepared for the Department of Canadian Heritage